Pobreza multidimensional nos municípios brasileiros no ano de 2010: uma aplicação dos conjuntos Fuzzy - Brites, Maríndia (2017)
Poverty is the worst form of human deprivation. The literature on poverty has gone through advances, since the traditional way of measuring poverty through monetary income does not capture all forms of deprivation suffered by people. The advancement of the concept of poverty is to include other important dimensions of people's lives; from the one-dimensional approach to the multidimensional approach. This dissertation, based on Capability Approach of Sen (1981, 1988, 2000), aims to measure multidimensional poverty for Brazilian cities in 2010. Using data from the Census (IBGE), which involved the choice of 16 indicators, five types of indices were constructed: the first four for each of the dimensions (housing conditions, income, access to knowledge and education and health and sanitary conditions), and the last one for the aggregated IFP, through Fuzzy Set Theory that allowed to approach poverty as a complex phenomenon and to generate the relative index of poverty. The results indicate that there is greater poverty in terms of health and sanitary conditions. However, the dimensions of access to knowledge and education and housing conditions also had weight in the multidimensional poverty index. The income dimension is one of less deprivation among cities, which emphasizes the importance of addressing and measuring poverty multidimensionally. The indicators with the greatest deprivations and that deserve greater attention on the part of the public managers are microcomputer with access to internet, washing machine, schooling and the type of sanitary sewage. The characteristics of poverty in the dimensions studied were similar and showed that the regions and states have similar poverty profiles, indicating that the North and Northeast of the country are the regions with the highest number of cities in the situation of very high and high poverty.